The Assessment: Trade and Location. - Venables, A (1998)
This paper gives an overview of different analyses of the effects of globalization on industrial location. It suggests that comparative advantage is inadequate to explain several aspects of the changing patterns of trade and location, and that it needs to supplemented by approaches based on new economic geography and theories of cumulative causation.